Impaired Neurobehavioural Performance in Untreated Obstructive Sleep Apnea Patients Using a Novel Standardised Test Battery - D'Rozario, Angela L.; Field, Clarice J.; Hoyos, Camilla M.; Naismith, Sharon L.; Dungan, George C.; Wong, Keith K. H.; Grunstein, Ronald R.; Bartlett, Delwyn J. (Frontiers in Surgery, 2018)
Objective/Background Although polysomnography (PSG) is the gold-standard measure for assessing disease severity in obstructive sleep apnea (OSA), it has limited value in identifying individuals experiencing significant neurobehavioural dysfunction. This study used a brief and novel computerised test battery to examine neurobehavioural function in adults with and without OSA. Patients/Methods 204 patients with untreated OSA (age 49.3 ± 12.5 years; body mass index (BMI) 33.6 ± 8.0 kg/m2; Epworth sleepiness scale (ESS, /24) 12 ± 4.9; apnoea hypopnea index 33.6 ± 25.8/h) and 50 non-OSA participants (age 39.2 ± 14.0 years; BMI 25.8 ± 4.2kg/m2, ESS 3.6 ± 2.3). All participants completed a computerised neurobehavioural battery during the daytime in the sleep clinic. The OSA group subsequently underwent an overnight PSG. The 30-min test battery assessed cognitive domains of visual spatial scanning and selective attention (Letter Cancellation Test), executive function (Stroop task) and working memory (2- and 3-Back tasks), and a validated sustained attention task (psychomotor vigilance task, PVT). Group differences in performance were compared. Associations between disease severity and performance were examined in the OSA group. Results After controlling for age, gender and education, OSA patients demonstrated impaired performance on the Stroop-Text, 2 and 3-Back tasks, and the PVT compared with the non-OSA group. OSA patients had worse performance on the LCT with fewer average hits albeit with better accuracy. Some OSA polysomnographic disease severity measures were weakly correlated with performance. Conclusions This brief test battery may provide a sensitive, standardised method of assessing daytime dysfunction in OSA.